Chemical Recovery of Degraded Soil and Consequence in the Cost of Corn Production - Wolschick, Neuro Hilton; Bertol, Ildegardis; Bagio, Bárbara; Wroblescki, Filipe Antonio; Bernardi, Loriane (Brazilian Archives of Biology and Technology, 2020)
Abstract Improper management degrades the soil, decreases corn productivity and is reflected in the cost of production. The objective of this research was to evaluate the soil recovery in non-conservationist treatments after the change of management and cultivation to the conservation condition direct sowing, and compare these systems to consolidated direct seeding; This evaluation was based on the soil responsiveness to crop production and water erosion control, and based on the financial cost of soil recovery and corn production when soil management was converted from non-conservationist (tillage rotation - RT, minimum tillage - MT, conventional tillage - CT and bare soil - BS) to no-tillage (NT) condition, in a Humic Cambisol. The transition from managements to no-tillage occurred in 2015 year, after 27 years of conducting the preexisting managements. The chemical recovery was carried out with the application of limestone, phosphorus, and potassium. At the end of the research the yield of the corn crop, the cost of recovering the soil fertility and the cost of crop production were evaluated. Previous soil management influenced the cost of soil chemical recovery. The cost of production showed a financial loss for the previous treatments CT and BS, on the average of the three corn crops.